2009
DOI: 10.1172/jci39269
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of premature immune aging in patients thymectomized during early childhood

Abstract: While the thymus is known to be essential for the initial production of T cells during early life, its contribution to immune development remains a matter of debate. In fact, during cardiac surgery in newborns, the thymus is completely resected to enable better access to the heart to correct congenital heart defects, suggesting that it may be dispensable during childhood and adulthood. Here, we show that young adults thymectomized during early childhood exhibit an altered T cell compartment. Specifically, abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 223 publications
(243 citation statements)
references
References 56 publications
14
226
0
3
Order By: Relevance
“…3B). This finding is reminiscent of results regarding relative numbers of memory T cells compared with naive T cells that have suggested CMV infection induces premature immune aging (34,35).…”
Section: Resultssupporting
confidence: 65%
“…3B). This finding is reminiscent of results regarding relative numbers of memory T cells compared with naive T cells that have suggested CMV infection induces premature immune aging (34,35).…”
Section: Resultssupporting
confidence: 65%
“…29,31,32 In thymectomized young adults this pattern was strongly associated with seropositivity to CMV. 33 Kohler et al showed that the surface molecule CD31 (PECAM-1) can be used to discriminate between CD31C thymic naive and CD31¡ central naive CD4C T-cells in the peripheral blood of healthy humans. 31 Both CD31C thymic naive and CD31¡ central naive CD4C T-cells satisfy phenotypic and functional criteria for naive CD4C T-cells: expression of surface markers, such as CD45RA, CD27, CD28, CCR7 and CD62L and secretion of IL-2 without significant effector cytokine production (interferon-g and IL4) after stimulation.…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 99%
“…Les jeunes adultes thymectomisés à la naissance représentent un groupe particulièrement informatif pour étudier les conséquences à long terme d'une thymectomie précoce et ainsi éva-luer l'importance du thymus au-delà de la production initiale du stock de cellules T. Des études préalables ont montré que les enfants thymectomisés avaient un nombre réduit de lymphocytes CD4 + et de TREC (TcR excision circle) 1 par rapport à un groupe contrôle [3-5] et que la réduction du nombre de cellules CD4 naïves était corrélée au temps écoulé depuis la thymectomie [6]. Nos propres travaux, menés chez 25 jeunes adultes (18 à 26 ans) ayant subi une ablation complète du thymus à la naissance lors d'une intervention correctrice d'une transposition des gros vaisseaux, révèlent également des altérations immunologiques assez profondes [7].…”
Section: La Fonction Thymiqueunclassified
“…Nous avons démontré que ce phé-notype immunitaire altéré était lié à une infection par le cytomégalovirus (CMV) et en particulier à l'établissement d'une réponse immunitaire cellulaire contre ce virus. Celle-ci est mise en évidence par la mesure de la sécrétion d'IFN (interféron)- en réponse aux peptides chevauchants recouvrants pp65 et IE1 [7]. On sait que cet herpès virus, qui est très prévalent dans la population générale et entraîne une infection persistante de son hôte, induit une très forte expansion des cellules mémoires T [8] associée à un recrutement continu du compartiment de cellules naïves [9].…”
Section: La Fonction Thymiqueunclassified
See 1 more Smart Citation